2002
DOI: 10.4049/jimmunol.168.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple Isolated Lymphoid Follicles on the Antimesenteric Wall of the Mouse Small Intestine

Abstract: We have revealed that 100–200 clusters, filled with closely packed lymphocytes, can be found throughout the length of the antimesenteric wall of the mouse small intestine. They are composed of a large B cell area, including a germinal center, and epithelia overlying the clusters contain M cells. A large fraction of B cells displays B220+CD19+CD23+IgMlowIgDhighCD5−Mac-1− phenotype, and the composition of IgA+ B cells is smaller but substantial. To our knowledge, these clusters are the first identification of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
422
2
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 429 publications
(454 citation statements)
references
References 34 publications
23
422
2
5
Order By: Relevance
“…It could alternatively occur in isolated B lymphoid follicles along the gut, as has been described for other species (see below). A [40] [ 41] similar pre-activated stage has been described for NK T cells , and, similarly to them, pre-activation of marginal zone B cells could be [42] driven by self or bacterial commensal antigens. For both these cellular populations, NKT and marginal zone B cells which are intermediate between the innate and adaptive immune system, this pre-activated stage may explain why they react very rapidly upon challenge by external bacterial antigens .…”
Section: A Proposed Explanationmentioning
confidence: 67%
“…It could alternatively occur in isolated B lymphoid follicles along the gut, as has been described for other species (see below). A [40] [ 41] similar pre-activated stage has been described for NK T cells , and, similarly to them, pre-activation of marginal zone B cells could be [42] driven by self or bacterial commensal antigens. For both these cellular populations, NKT and marginal zone B cells which are intermediate between the innate and adaptive immune system, this pre-activated stage may explain why they react very rapidly upon challenge by external bacterial antigens .…”
Section: A Proposed Explanationmentioning
confidence: 67%
“…6 -8 An ILF is a single B-cell follicle that develops a germinal center on maturation and can serve as an inductive site for IgA responses. 9,10 A single ILF fills up an entire villus and is covered by a follicleassociated epithelium (FAE) containing M cells, that is similar to the FAE of PPs. A normal adult mouse has approximately 100 to 200 ILFs in the small intestine and 50 in the colon.…”
mentioning
confidence: 99%
“…A normal adult mouse has approximately 100 to 200 ILFs in the small intestine and 50 in the colon. 9 Recently, it has been suggested that CPs and ILFs are not distinct types of intestinal lymphoid tissue, but rather two extremes on a continuum of solitary intestinal lymphoid tissue (SILT). 11 Current evidence suggests that the number of SILT structures in the intestine is normally stable after postnatal development is completed.…”
mentioning
confidence: 99%
“…A recent study revealed the existence of isolated lymphoid follicles (ILF) in the small intestine that resemble PP in terms of architecture and cellular composition (8). The fact that ILF possess germinal centers and an overlying follicle-associated epithelium (FAE) containing M cells suggests their possible role as mucosal inductive sites (8).…”
mentioning
confidence: 99%
“…It had been believed that PP is the major inductive site for the initiation of Ag-specific IgA responses to a variety of exogenous Ag (3,4); however, we and others have demonstrated that PP contribute to, but are not essential for, the induction of Agspecific mucosal IgA responses (5)(6)(7). A recent study revealed the existence of isolated lymphoid follicles (ILF) in the small intestine that resemble PP in terms of architecture and cellular composition (8). The fact that ILF possess germinal centers and an overlying follicle-associated epithelium (FAE) containing M cells suggests their possible role as mucosal inductive sites (8).…”
mentioning
confidence: 99%